Analysis of data arrays on cyclotron production of medical radioisotopes - Petrusenko, Yu.T.; Lymar, A.G.; Nikolaichuk, L.I.; Tutubalin, A.I.; Shepelev, A.G.; Ponomarenko, T.A.; Nemashkalo, O.V. (Вопросы атомной науки и техники, 2009)
The paper analyzes the state of cyclotron production of radionuclides (RN) for nuclear medicine. Consideration is given to the production of ultra-short-lived (USL) and short-lived (SL) RN. The information of the IAEA Database "International Nuclear Information Systems" (INIS) for a period from 1970 to 2007 has been used for the analysis. The paper reports the data on the dynamics of works published about the cyclotron production of USL and SL RN, kinds of the works, and also, on the relative contribution of different countries to the total number of published works. Conclusions are drawn about the trends in the research of the problems considered. Наведено аналіз стану виробництва на циклотронах радіонуклідів (РН) для ядерної медицини. Розглядається проблема отримання ультрокороткоживучих (УКЖ) та короткоживучих (КЖ) РН. При аналізі використовувалася інформація, що міститься у Міжнародній Базі Даних МАГАТЕ "International Nuclear Information System" (INIS) за період з 1970 по 2007 р. Приведено результати відносно динаміки публікацій з виробництва циклотронних УКЖ і КЖ РН, відносно вигляду публікацій, а також відносно вкладу різних країн в загальне число публікацій. Зроблено висновки відносно тенденції розвитку досліджень з розглянутих питань. Дан анализ состояния производства на циклотронах радионуклидов (РН) для ядерной медицины. Рассматривается проблема получения ультрокороткоживущих (УКЖ) и короткоживущих (КЖ) РН. При анализе использовалась информация, содержащаяся в Международной Базе Данных МАГАТЭ "International Nuclear Information System" (INIS) за период с 1970 по 2007 г. Приводятся сведения о динамике публикаций по производству циклотронных УКЖ и КЖ РН, о виде публикаций, а также об относительном вкладе различных стран в общее число публикаций. Сделаны заключения о тенденции развития исследований по рассмотренным вопросам.